Underestimated Factors Regarding the Use of Technology in Daily Practice of Long-Term Care: Qualitative Study Among Health Care Professionals - Sjors W M Groeneveld; Marjolein E M den Ouden; J E W C van Gemert-Pijnen; Rudolph M Verdaasdonk; Harmieke van Os-Medendorp (JMIR Publications, 2023)
BackgroundIncreasing life expectancy is resulting in a growing demand for long-term care; however, there is a shortage of qualified health care professionals (HCPs) to deliver it. If used optimally, technology can provide a solution to this challenge. HCPs play an important role in the use of technology in long-term care. However, technology influences several core aspects of the work that HCPs do, and it is therefore important to have a good understanding of their viewpoint regarding the use of technology in daily practice of long-term care. ObjectiveThe aim of this study was to identify the factors that HCPs consider as relevant for using technology in daily practice of long-term care. MethodsIn this qualitative study, 11 focus groups were organized with 73 HCPs. The focus group discussions were guided by an innovative game, which was specifically developed for this study. The content of the game was categorized into 4 categories: health care technology and me; health care technology, the patient, and me; health care technology, the organization, and me; and facilitating conditions. The perspectives of HCPs about working with technology were discussed based on this game. The focus groups were recorded and transcribed, followed by an inductive thematic analysis using ATLAS.ti 9x (ATLAS.ti Scientific Software Development GmbH). ResultsOverall, 2 main domain summaries were developed from the data: technology should improve the quality of care and acceptance and use of technology in care. The first factor indicates the need for tailored and personalized care and balance between human contact and technology. The second factor addresses several aspects regarding working with technology such as trusting technology, learning to work with technology, and collaboration with colleagues. ConclusionsHCPs are motivated to use technology in daily practice of long-term care when it adds value to the quality of care and there is sufficient trust, expertise, and collaboration with colleagues. Their perspectives need to be considered as they play a crucial part in the successful use of technology, transcending their role as an actor in implementation. On the basis of the findings from this study, we recommend focusing on developing technology for situations where both efficiency and quality of care can be improved; redefining the roles of HCPs and the impact of technology hereon; involving HCPs in the design process of technology to enable them to link it to their daily practice; and creating ambassadors in care teams who are enthusiastic about working with technology and can support and train their colleagues.